The Silkworm Girl, Sericultural EcoGothic, and the Anthropocene - Li-hsin Hsu (Nuevas Poligrafías, Revista de Teoría Literaria y Literatura Comparada)
The article looks at the connection between Chinese folklores and the Anthropocene, examining the tale of the silkworm girl in ancient Chinese mythologies and folklores from an EcoGothic perspective of human-nonhuman alliance (as well as its betrayal). The process of sericultural development in Asia works in tandem with the formation of the renowned “silk road,” an international commercial (as well as military) route for the exchange of goods and materials from East Asia and Central Asia to Europe and the Mediterranean region. The myth of the silkworm girl encapsulates an eco-economic co-existence among human beings, animals, plants, and matter in its most rudimentary form. My discussion focuses on the two versions of the story of the silkworm girl, one from an earlier collection of folklore—Sou shen ji (In Search of the Supernatural: The Written Record) by Jin Dynasty historian, Bao Gan, in China—and the other one by Guan Ting Du—Yong Cheng Ji Sian Lu (Records of the Assembled Transcendents of the Fortified Walled City), a later collection of stories compiled in the Tang dynasty. While silkworms in ancient Chinese literature and the sericulture they embody have been associated with agricultural advancement through the human domestication and extraction of natural resources, the anthropocentric interpretations of the moral lessons conveyed in those tales about the economic value their industry and productivity symbolize is problematized by the girl-horse metamorphosis and their symbiotic relationship with mulberry trees. Their representations are further complicated by the military involvement in sericulture. This article compares diverging representations of the silkworm girl within the context of the sericultural practice, particularly the man-horse-silkworm-mulberry entanglement, to reconsider the ecological significance of Asian mythologies in the age of our Anthropocene crisis.